2014
DOI: 10.1063/1.4898587
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled inversion of tunnel magnetoresistance in epitaxial nickel/graphene/MgO/cobalt junctions

Abstract: Spin-based memory and logic devices are the subject of an intense research activity motivated by the perspective to overcome power, performance and architectural bottlenecks of CMOS-based devices. Among potential material candidates in this field, graphene (Gr) carries great expectations because of its unique electronic transport properties. So far, graphene has been employed mainly in "lateral" spintronic devices, where ferromagnetic electrodes are deposited on top of graphene and electron current flows in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 36 publications
3
49
1
Order By: Relevance
“…3 While its exact origin is still under study, 24 the increase of spin polarization with the number of layer is in agreement with the reported predictions of Karpan et al 25 and more recently Laczic et al 26 We note that the observed negative sign of the magneto-resistance and its amplitude has been observed reproducibly.…”
supporting
confidence: 79%
“…3 While its exact origin is still under study, 24 the increase of spin polarization with the number of layer is in agreement with the reported predictions of Karpan et al 25 and more recently Laczic et al 26 We note that the observed negative sign of the magneto-resistance and its amplitude has been observed reproducibly.…”
supporting
confidence: 79%
“…Spin filtering across a 2D material was first theoretically proposed by Karpan et al 143,144 , who predicted that graphene or graphite on lattice matched surfaces of nickel or cobalt behaves like a half-metal and can be used to inject 100% spin polarized current in to nonmagnetic conductors. Rather low values of magnetoresistance were found experimentally due to disorder at FM/graphene interface [145][146][147][148] . Thereafter, it was predicted that due to almost perfectly matched in-plane lattice constants of graphene and hBN, a FM/fewlayergraphene/hBN junction can act as an ideal spin filter with an increased R c A product [149][150][151] , which is essential for avoiding the conductivity mismatch problem for efficient spin injection in graphene 152 .…”
Section: B Spin Filtering Across Hbn/graphene Interfacementioning
confidence: 97%
“…Recently, graphene has been explored as a barrier for spin transport, where TMR and spin filtering effects have been observed [9][10][11][12][13][14][15][16][17][18][19], including the bias dependence of the TMR [20]. However, the absence of a bandgap in semi-metallic and low resistive graphene has led to an increasing demand for an insulating 2D crystal [7][8][9].…”
Section: Introductionmentioning
confidence: 97%